2017
DOI: 10.1111/cdev.12933
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Campus Support, Undocumented Identity, and Deferred Action for Childhood Arrivals on Civic Engagement for Latinx Undocumented Undergraduates

Abstract: This study examined civic engagement in a sample of 790 undocumented Latinx undergraduates (aged 18-30). The relations between social supports (campus safe spaces and peer support) and civic engagement and whether a strong sense of undocumented identity mediated this relation were examined. Competing statistical models examined the role of participants' status (whether or not they received temporary protection from deportation with Deferred Action for Childhood Arrivals [DACA]) in this mediational process. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Undocumented youth in higher education may be particularly vulnerable to discrimination, as they are more likely to associate with individuals from other racial/ethnic groups, thereby developing a racial identity as ascribed by the U.S.'s complex racial dynamics (Abraído-Lanza et al, 2016). They may also face immigration-related discrimination on campus in the form stigma, racist nativist microagressions, and institutional neglect (Katsiaficas et al, 2019;Muñoz & Vigil, 2018).…”
Section: Discriminationmentioning
confidence: 99%
“…Undocumented youth in higher education may be particularly vulnerable to discrimination, as they are more likely to associate with individuals from other racial/ethnic groups, thereby developing a racial identity as ascribed by the U.S.'s complex racial dynamics (Abraído-Lanza et al, 2016). They may also face immigration-related discrimination on campus in the form stigma, racist nativist microagressions, and institutional neglect (Katsiaficas et al, 2019;Muñoz & Vigil, 2018).…”
Section: Discriminationmentioning
confidence: 99%
“…Some DACA youth respond to structural violence by engaging in activism and giving back to their community. For example, researchers found high levels of civic engagement among undocumented and DACA youth, and that among DACA youth, a stronger undocumented identity was directly related to higher civic engagement (Katsiaficas et al, 2019). Past research found that DACA youth engage in everyday forms of activism, such as raising awareness about DACA and giving back to their community (Getrich, 2021).…”
Section: History Of Dacamentioning
confidence: 99%
“…As a result, immigrant students often take on educator roles in addition to their student responsibilities. For instance, they may educate faculty about undocumented and DACA students [18]. DACA students are classified as international students despite not living in their country of origin.…”
Section: Literature Reviewmentioning
confidence: 99%